2014
DOI: 10.1590/s1984-29612014071
|View full text |Cite
|
Sign up to set email alerts
|

Study on coinfecting vector-borne pathogens in dogs and ticks in Rio Grande do Norte, Brazil

Abstract: Since dogs presenting several vector borne diseases can show none or nonspecific clinical signs depending on the phase of infection, the assessment of the particular agents involved is mandatory. The present study aimed to investigate the presence of Babesia spp., Ehrlichia spp., Anaplasma spp., Hepatozoon spp. ResumoCães que apresentam diversas doenças transmitidas por vetores podem mostrar nenhum ou alguns sinais clínicos inespecíficos. Dependendo da fase da infecção, a confirmação dos agentes envolvidos é … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 43 publications
1
13
0
2
Order By: Relevance
“…En Perú, R. microplus se ha reportado como un parásito del ganado y, en Brasil, R. sanguineus se considera un parásito de perros, así como potencial vector de L. infantum (19)(20)(21) y L. braziliensis (20). Debe señalarse, además, que en estudios anteriores en Italia y Brasil se encontraron porcentajes más Figura 3.…”
Section: Discussionunclassified
“…En Perú, R. microplus se ha reportado como un parásito del ganado y, en Brasil, R. sanguineus se considera un parásito de perros, así como potencial vector de L. infantum (19)(20)(21) y L. braziliensis (20). Debe señalarse, además, que en estudios anteriores en Italia y Brasil se encontraron porcentajes más Figura 3.…”
Section: Discussionunclassified
“…In Brazil, although species genetically related to H. americanum have been described parasitizing wild canids (CRIADO-FORNELIO et al, 2006;ANDRÉ et al, 2010), only H. canis has been detected in domestic dogs (PALUDO et al, 2005;MUNDIM et al, 2008;RAMOS et al, 2010;GONÇALVES et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…We observed 100% identicalness between our sequences with H. canis from Croatia and other regions of Brazil, suggesting either a geographic expansion of this infection or a recent increase in the efficiency in detecting these parasites. Recently, canine hepatozoonosis has been described in several Brazilian regions (RUBINI et al, 2008;MIRANDA et al, 2014;GONÇALVES et al, 2014;RAMOS et al, 2015;DEMONER et al, 2016). Many of these areas are also endemic for CVL and co-infection was indeed described in dogs from Rio Grande do Norte, but only through molecular analysis (GONÇALVES et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular characterization indicated that Brazilian H. canis was closely related to isolates from Japan, presented 99% nucleotide identity with isolates from Israel and was found to be distantly related to H. americanum (RUBINI et al, 2005). In the following years, canine hepatozoonosis has also been described in several Brazilian regions (RUBINI et al, 2008;MIRANDA et al, 2014;GONÇALVES et al, 2014;RAMOS et al, 2015;DEMONER et al, 2016). Many of these areas are also endemic for CVL, and co-infection has already been described in dogs from Rio Grande do Norte based only on molecular analyses (GONÇALVES et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation